Thermal acclimation of tropical coral reef fishes to global heat waves - Johansen, Jacob L; Nadler, Lauren E; Habary, Adam; Bowden, Alyssa J; Rummer, Jodie (eLife, 2021)
As climate-driven heat waves become more frequent and intense, there is increasing urgency to understand how thermally sensitive species are responding. Acute heating events lasting days to months may elicit acclimation responses to improve performance and survival. However, the coordination of acclimation responses remains largely unknown for most stenothermal species. We documented the chronology of 18 metabolic and cardiorespiratory changes that occur in the gills, blood, spleen, and muscles when tropical coral reef fishes are thermally stressed (+3.0°C above ambient). Using representative coral reef fishes (Caesio cuning and Cheilodipterus quinquelineatus) separated by >100 million years of evolution and with stark differences in major life-history characteristics (i.e. lifespan, habitat use, mobility, etc.), we show that exposure duration illicited coordinated responses in 13 tissue and organ systems over 5 weeks. The onset and duration of biomarker responses differed between species, with C. cuning – an active, mobile species – initiating acclimation responses to unavoidable thermal stress within the first week of heat exposure; conversely, C. quinquelineatus – a sessile, territorial species – exhibited comparatively reduced acclimation responses that were delayed through time. Seven biomarkers, including red muscle citrate synthase and lactate dehydrogenase activities, blood glucose and hemoglobin concentrations, spleen somatic index, and gill lamellar perimeter and width, proved critical in evaluating acclimation progression and completion, as these provided consistent evaluation of thermal responses across species.
Keywords: temperature; global climate change; fish; plasticity; physiology; stenotherm